The challenge of unemployment to development and the role of training and research institutes in development: meeting of Directors of Development Training and Research Institutes, Motebello (Quebec), Canada, 13th - 17th July, 1970 - Organisation for Economic Co-operation and Development (Paris : Development Centre of the Organization for Economic Cooperation and Development, 1971)
This book examines the effects of unemployment on economic development. It also highlights the benefits of research institute for national growth and development.
"Meeting of Directors of Development Training and Research Institutes, Montebello (Quebec), Canada, 13th-17th July, 1970."
Includes bibliographical references.
asm 14/02/19
Loans
Keywords: Unemployment; Manpower policy; Occupational training